Investigating The Effect of Green Bonds on Firm’s Environmental Performance and Shareholder’s Wealth - Asty Purbasari (Management Analysis Journal, 2025)
Despite its significant growth, the effect of corporate green bonds on environmental and financial performance in Indonesia is still under-researched. This paper is designed to answer the questions of whether environmental awareness drives companies to raise capital for green projects and, more importantly, whether issuing green bonds is effective to improving the companies’ environmental and financial performance. Using desk reviews from public documents, this study examines green bonds issued by ten Indonesian companies during 2018–2023. It is found that all green bond issuers have climate targets and measures to reduce sustainability risks and that the fund proceeds are associated with climate change adaptation. However, it is unclear in which green bonds can really serve as a bridge between companies’ environmental motives to improve environmental performance. Although the link is uncertain, the study further finds financial improvements with regards to the cost of debt, return on equity, and stock return.